Устройство для измерения расстройки компенсации емкостного тока замыкания на землю - Вайнштейн Р. А. Роберт Александрович; Березницкий С. Л.; Шестакова В. В. Вера Васильевна; Юдин С. М. Святослав Михайлович
опубл. 27.04.04